Where is the Target? An Examination of the Conceptions of Student Engagement within a School Community - Gary Andersen; Linda E Feldstein Ed. D. (Educational Considerations, 2021)
In 2017, the Kansas State Department of Education (KSDE) launched an ambitious school redesign project. High Plains High School (pseudonym) was among the schools selected for redesign, and as part of their plan, High Plains High School (HPHS) faculty and staff administered a survey to students. Survey results indicated approximately 38% of students felt “disengaged” at school. HPHS administrators found these results worthy of study, in an attempt to understand how students, faculty, and families were conceptualizing school engagement. Results indicate that each constituency tended toward differing concepts of what it means to be engaged in the classroom. Implications include the need for teacher educators to more deeply address preservice students’ understanding of engagement, as well as a shift to a conceptual understanding of student engagement that is more agentic. Results could catalyze changes in educator preparation programs to improve candidates’ understanding of engagement and its role in student success.
Keywords: engagement; school engagement; student engagement; agentic engagement; behavioral engagement; cognitive engagement; social engagement; emotional engagement; rural schools; school reform; school redesign